FINLOGIC.@STATEMENTS - Norizan, Saifulrizan; Noyem, Josephine Avelind; Rahmat, Mariam; Awang Bolhan, Dayangku Ruhayah; Keska, Gibson Gary Leman (2025)
FINLOGIC.@STATEMENTS is a web-based digital learning platform developed to enhance the comprehension of financial reporting concepts such as double-entry bookkeeping, the Statement of Financial Position, the Statement of Profit or Loss, and the Statement of Cash Flow. Initially released as a mobile app, the tool evolved into a comprehensive, browser-based system after receiving high demand from academic institutions and learners. It provides an interactive, simulation-driven, and gamified learning experience that aims to bridge the gap between theoretical accounting knowledge and practical application. By incorporating interactive tools such as real-time transaction simulation and dynamic statement generation, FINLOGIC.@STATEMENTS helps learners and professionals visualize financial data flows, enabling them to grasp accounting principles more intuitively. The platform aligns with modern educational standards and pedagogies and is well-positioned for institutional integration. Furthermore, its scalability and adaptability present significant commercialization opportunities across education, corporate training, and public-sector financial literacy initiatives.